2022
DOI: 10.3390/foods11050681
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Chemical Characterisation of Conventional and Nano/Emulsions: Influence of Vegetable Oils from Different Origins

Abstract: The processes of oil production play an important role in defining the final physical and chemical properties of vegetable oils, which have an influence on the formation and characteristics of emulsions. The objective of this work was to investigate the correlations between oils’ physical and chemical properties with the stability of conventional emulsions (d > 200 nm) and nanoemulsions (d < 200 nm). Five vegetable oils obtained from different production processes and with high proportion of unsaturated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 85 publications
2
16
0
Order By: Relevance
“…On the other hand, PG NEs were semi-transparent, due to very fine droplet sizes (Z-ave < 65 nm), also with notable differences between blank NE (F0 PG: 62.32 nm) and RO-loaded NEs (38.63–46.56 nm). Droplet size distribution was very narrow (PDI < 0.15) in both types of NE systems (i.e., 0.116–0.125 for P80 NEs, and 0.051–0.110 for PG NEs, respectively), indicating good preliminary stability [ 26 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, PG NEs were semi-transparent, due to very fine droplet sizes (Z-ave < 65 nm), also with notable differences between blank NE (F0 PG: 62.32 nm) and RO-loaded NEs (38.63–46.56 nm). Droplet size distribution was very narrow (PDI < 0.15) in both types of NE systems (i.e., 0.116–0.125 for P80 NEs, and 0.051–0.110 for PG NEs, respectively), indicating good preliminary stability [ 26 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the main reasons for increased instability of oil in emulsion system compared to bulk oil is a large contact area between the oil and the water phase containing prooxidants. Moreover, previous studies showed that structural and physicochemical properties of surfactants, as well as their interactions with antioxidants in formulations, significantly influence oxidative stability of emulsified oils [ 23 , 25 , 26 , 45 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations